Respuesta :
Answer:
No. He wrong in the 1st step . The value of x is -7 and 0 .
Step-by-step explanation:
In order to solve the equation, you have to make the equation equals to zero by substracting 12 to both sides :
[tex] {x}^{2} + 7x + 12 = 12[/tex]
[tex] {x}^{2} + 7x + 12 - 12 = 12 - 12[/tex]
[tex] {x}^{2} + 7x = 0[/tex]
Next, you have to factorize and solve it :
[tex]x(x + 7) = 0[/tex]
[tex]x = 0[/tex]
[tex]x + 7 = 0 \\ x = - 7[/tex]
Answer:
Percy is not correct because he applied the zero product property to a factored expression that was not equal to 0. He should have subtracted 12 from both sides to get x2 + 7x = 0 before factoring. The correct solutions are 0 and -7.
Step-by-step explanation:
Sample response for edge lol